PENGARUH KEPATUHAN PROTOKOL KESEHATAN PANDEMI COVID - 19 TERHADAP STRES DAN RELIGIUSITAS MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - MUHAMMAD IQBAL; DES SURYANI; NANDA SARI NURALITA; PINTA PUDIYANTI SIREGAR (LP2MTBM MAKARIOZ, 2021)
COVID-19 is an infectious disease outbreak that has emerged since January 30, 2019 and has been called a public healthemergency by WHO. In order to avoid community transmission, it is recommended to comply with the health protocolestablished by the government. Many of the impacts of the health protocol are felt by the community, especially students,namely academic stress. The level of adherence to the health protocol itself can be related to the level of one's religiosity.To determine the effect of compliance with the COVID-19 health protocol on stress and religiosity of students at the Facultyof Medicine, University Muhammadiyah of Sumatra Utara. This study is a cross-sectional study. The number of sampleswas calculated using the Slovin formula totaling 164 people. Hypothesis test used is Chi Square test. Data were collectedbased on a questionnaire, namely DASS-42, adherence to health protocols and the Religiosity Scale. The results showedthat during the pandemic the level of good student compliance was 52.4% and those who did not comply were 47.6% with anormal stress level of 68.3% , mild stress 15.2%, moderate stress 9.8%, heavy stress 4.9% and very severe stress 1.8%.The level of religiosity of students during the pandemic with good religiosity was 51.2% and those that were lacking were48.8%. Based on the Chi Square test, it was found that the relationship between health protocol compliance with stress (p =0.001) and religiosity (p value = 0.001) but after the Kendall's tau correlation test, the value of p = 0.001 and p = 0.001 wasfound (it seems that there is a positive relationship with very strong correlation. weak. Adherence to implementing healthprotocols has a positive correlation with religiosity and student stress, but the correlation is weak. There is a positiveinfluence between compliance with the COVID-19 protocol on stress and religiosity.